Dialektika Relasional Gen Z Pada Era Always-on di Kabupaten Sleman (Studi Kualitatif Dialektika Relasional dalam Komunikasi Interpersonal Negosiasi Batas Peran Gen Z Pada Era Always-on di Kabupaten Sleman,Yogyakarta) - Dela Esti Maulidiya; Aurelia Retno Wulan; Tri Utari Wardayani (CV. ITTC INDONESIA, 2026)
This study aims to understand how Generation Z negotiates the boundaries between their professional and personal lives through interpersonal communication in the ‘always-on’ era in Sleman Regency. The study employs a descriptive qualitative approach, using Baxter and Montgomery’s Relational Dialectics Theory as the basis for analysis. Data were collected through in-depth interviews, observation and documentation involving seven Generation Z informants aged 17–26 who work in Sleman Regency, Yogyakarta. Data analysis utilised the Miles and Huberman model, which encompasses data reduction, data presentation and drawing conclusions. The findings indicate that Generation Z’s communication responses are dynamic and influenced by the urgency of the message, work experience, technological developments, and personal circumstances. The study also identified a tension between the demands of professionalism and the need to maintain personal space. To manage this tension, the informants employed various communication strategies, such as selective responses, managing notifications, using auto-replies, and delaying responses. These findings suggest that role boundaries are constructed through a process of ongoing communicative negotiation.